2020
DOI: 10.1111/his.14181
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐infiltrating lymphocytes in ductal carcinoma in situ (DCIS)—assessment with three different methodologies and correlation with Oncotype DX DCIS Score

Abstract: Tumour-infiltrating lymphocytes in ductal carcinoma in situ (DCIS)-assessment with three different methodologies and correlation with Oncotype DX DCIS Score Aims: Tumour-infiltrating lymphocytes (TILs) are prognostic in invasive breast cancer; however, their prognostic significance in ductal carcinoma in situ (DCIS) has not been established. The Oncotype DX (ODX) Breast DCIS Score test is a genomic assay used to predict the local recurrence risk. The aims of this study were to quantify TILs in DCIS by the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Furthermore, Komforti et al revealed that the presence of touching-TILs (>5 touching TILs per DCIS duct) was significantly associated with high or intermediate Oncotype DCIS Score, hence worse outcomes in DCIS. 32 In several previous studies, the intrinsic immunological associations between dense TILs and worse prognosis in the DCIS population have been preliminarily described. In a study enrolling 138 patients with pure DCIS, both the fraction of the genome altered (FGA) and the number of telomeric imbalances were found to be positively associated with touching-TILs (both p < .001), which implies that the touching-TILs could be influenced by the antigens produced by copy number variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Komforti et al revealed that the presence of touching-TILs (>5 touching TILs per DCIS duct) was significantly associated with high or intermediate Oncotype DCIS Score, hence worse outcomes in DCIS. 32 In several previous studies, the intrinsic immunological associations between dense TILs and worse prognosis in the DCIS population have been preliminarily described. In a study enrolling 138 patients with pure DCIS, both the fraction of the genome altered (FGA) and the number of telomeric imbalances were found to be positively associated with touching-TILs (both p < .001), which implies that the touching-TILs could be influenced by the antigens produced by copy number variation.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of TILs in predicting cancer outcome has been reported in many studies [ 8 , 16 , 17 ]. A proposal for a standardised method to evaluate TILs in solid tumours using HE-stained sections was introduced recently [ 9 , 10 ] and a good reproducibility in different cancer types has been reported [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 198 cases with recurrence follow-up reported, a significant association between circumferential TILs and worse disease-free survival [ 40 ]. Recently, Komforti et al [ 24 ] assessed the pattern of TILs in a series of 97 cases by three different methodologies [ 20 , 23 , 41 ]. Stromal TILs showed the lowest concordance rate, followed by touching TILs by all pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…The observers were blinded to the clinical data. The amount and distribution of TILs were assessed using the previously described methodologies, including the estimation of stromal TILs, the estimation of TILs touching DCIS ducts, and the assessment of circumferential TILs and presence or absence of hotspots [ 23 , 24 ]. TILs associated with areas of necrosis, prior biopsy, and crush artefacts were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation